Total quality management: lessons for Latin America - Hodgetts, Richard (1994)
This paper intends to present a list of eight factors capable to contribute to the sucess of enterprises wishing to become leaders in their field of action, in accordance with the fundings of a recent study on how a group of American companies has won the Malcolm Baldridge Quality Award - MBQA, a premium annualy awarded by the American government to enterprises achieving a very high standard of quality.